Diagnóstico financiero y estudio de la rentabilidad en reyes cueva mercedes cumanda de la ciudad de Loja, periodo 2012 - Tandazo Díaz, Silvia Patricia (2016)
This paper was prepared based on the overall objective of creating a Financial Diagnosis and Study of Performance Reyes Cave Mercedes Cumanda City of Loja, period 2012, for which compliance was given to each of the objectives as a diagnosis financial , apply financial indicators to assess the financial position of the company, to conduct a study of return to determine the efficiency with which it has used the assets of the company. The methodology was based on the use of methods such as: scientific deductive , inductive, mathematical , statistical, analytical that enabled the realization of the aforementioned analysis. In conducting the analysis can determine that the company has on its balance sheet total current assets of $ 134,265.56 corresponding to 25.41% , where significant value in accounts receivable is observed with a value of $ 71541.95 with a percentage of 53.28 % so the company should improve its collection policies that allow recovering outstanding values thus increasing the cash in their accounts and in turn get to maintain a high rate of immediate liquidity , able to meet their obligations when required , improving their level of performance and efficiency in operations in non-current assets worth $ 394,157.85 with 74.59 % in observing that the account has a relevant vehicles worth $ 234,122.57 with 42.03 %, which is favorable for the company because it is necessary for the operation of the same , then we have detailing liabilities totaling $ 111,140.03 at the rate of 73.08 % and finally have heritage a total of $ 417,283.38 equivalent to 78.97 % in terms of detailed income statement with revenue totaling $ 2,145,421.69 with a percentage of 100 % is observed where the account selling fuels and lubricants has a significant value of $ 2,000,338.16 with a percentage of 93.24 %, which means that this year there have been used sales significantly and is therefore represents a great benefit to the company , and subsequently we have a total Expenses of $ 2,071,094.61 equivalent to 100% , also applied financial indicators that determined their potential for continued operation and solvency allows you to consider purchasing future obligations as it has sufficient capital and liquidity to cover cost . Finally the results shows that the company has high accounts receivable which has a significant value of $ 71,541.95 corresponding to 53.28 %, demonstrating that it has no collection policies necessary for the recovery of nonperforming loans , so that the owner is recommended to establish collection policies that allow you to recover outstanding values , thus increasing the cash in their accounts and in turn projected an index of more immediate liquidity to enable it to meet its obligations in a timely manner.